Communication power - Castells, Manuel, 1942- (Oxford University Press, 2011)
"We live in the midst of a revolution in communication technologies that affects the ways people feel, think, and behave. The media have become the space where power strategies are played out. In the current technological context mass communication goes beyond traditional media and includes the Internet and mobile communication." "In this book, Manuel Castells analyses the transformation of the global media industry by this revolution in communication technologies. He argues that a new communication system, mass self-communication, has emerged, and power relationships have been profoundly modified by the emergence of this new communication environment. Created in the commons of the Internet this communication can be locally based, but globally connected. It is built through messaging, social networking sites, and blogging, and is now being used by the millions around the world who have access to the Internet."--Book jacket.